Justice “cost points”: examination of privatization within public systems of justice - Harris, Alexes (Criminology & public policy, 2019)
In addition to outsourcing the management of correctional facilities, many local and state authorities contract with private companies to provide a variety of services and processes within U.S. courthouses, jails, and prisons. In this article, we explore the various “cost points” at which individuals who make contact with public systems of justice are charged by private entities. We provide two case studies with an in‐depth look at how private companies make money within U.S. justice facilities—court‐ordered programs and prison services.